The hidden inheritance - Keene, Carolyn; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 1996)
While doing a favor for her father in Bear Hollow, Indiana, Nancy tries to help a new friend find the reasons someone is trying to ruin her family. A long lost family secret and an inherited fiddle seem to hide clues to a secret fortune.
"A Minstrel book."
Keywords: Adventure -- fiction; Mysteries -- fiction; Mystery fiction